Effect of sulfur fertilization, varieties and irrigation scheduling on growth, yield, and heat utilization efficiency of indian mustard (Brassica Juncea L.). Issue 2 (19th January 2020) - Rana, Kiran; Parihar, Manoj; Singh, J P; Singh, Rajesh Kumar
ABSTRACT: A field experiment was conducted to evaluate the effect of sulfur fertilization and irrigation scheduling on mustard hybrids in Varanasi, India. Experiment comprised 18 treatment combination involving three irrigation scheduling (0.4, 0.6 and 0.8 IW/CPE) and two hybrids (NRCHB-506 and PAC 432) as main plot treatment and three sulfur (S) levels (0, 30 and 60 kg S ha −1 ) as sub-plot treatment in split-plot design replicated thrice during Rabi season (Oct–March) of 2015–16 and 2016–17. Statistical analysis of the results revealed that individually irrigation scheduling at 0.8 IW/CPE, mustard variety 'PAC 432ʹ and sulfur application at 60 kg ha −1 reported to have maximum plant height, number of primary and secondary branches, dry matter accumulation, number of siliquae plant −1, number of seeds siliqua −1, siliqua length and seed yield. Similar results were also obtained in relation to dry matter heat use efficiency (DM-HUE) at different stages and seed yield HUE. However, the variation in most of the parameters observed with either 0.6 or 0.8 IW/CPE and application of 30 or 60 kg S ha −1 was found non-significant during the course of the trial. In terms of interaction, mustard variety 'PAC 432ʹ irrigated at 0.8 and 0.6 IW/CPE and fertilized with 60 or 30 kg S ha −1 proved significantly superior over other treatments and recorded the highest plant height, better yield constituents and maximum yield, while the lowest values for the same were recorded in 'NRCHB-506ʹ irrigated at 0.4 IW/CPE with no sulfur application during both the years of experimentation.